2022
DOI: 10.1002/ece3.8976
|View full text |Cite
|
Sign up to set email alerts
|

Airport noise disturbs foraging behavior of Japanese pipistrelle bats

Abstract: The expansion of anthropogenic noise poses an emerging threat to the survival and reproductive success of various organisms. Previous investigations have focused on the detrimental effects of anthropogenic noise on the foraging behavior in some terrestrial and aquatic animals. Nevertheless, the role of airport noise in impairing foraging activities of most wild animals has been neglected. Here, we aimed to assess whether foraging behavior in free‐living Japanese pipistrelle bats ( Pipistrellus abra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Merbecoviruses are yet another type of beta-coronavirus found in wildlife with potential human cell compatibility and a possibility to cause severe disease in humans. Japanese house bats ( Pipistrellus abramus ) are the natural host for HKU5 coronaviruses and are synanthropic, roosting in human dwellings and structures, and therefore pose repeat opportunities for human exposure 46,58 . Luckily, clade 2 merbecovirus RBDs exhibit low human ACE2 compatibility, although efforts should still be made to reduce contact with these animals (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Merbecoviruses are yet another type of beta-coronavirus found in wildlife with potential human cell compatibility and a possibility to cause severe disease in humans. Japanese house bats ( Pipistrellus abramus ) are the natural host for HKU5 coronaviruses and are synanthropic, roosting in human dwellings and structures, and therefore pose repeat opportunities for human exposure 46,58 . Luckily, clade 2 merbecovirus RBDs exhibit low human ACE2 compatibility, although efforts should still be made to reduce contact with these animals (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we conclude that low SNR is not the only trigger for the Lombard effect, or the bats are still trying to maintain a perceptual SNR does not depend only on the carrier frequencies of the noise. Multiple field studies have shown that echolocating behavior is disturbed by anthropogenic noise, which is usually spectrally non-overlapping ( Siemers and Schaub, 2011 ; Bunkley et al, 2015 ; Bunkley and Barber, 2015 ; Luo et al, 2015 ; Wang et al, 2022 ). However, whether echolocating bats increase the intensity of their calls in response to spectrally non-overlapping noise under field conditions still needs to be verified.…”
Section: Discussionmentioning
confidence: 99%
“…Our present study shows that 60-dB SPL, 1- to 20-kHz white noise can potentially disturb the echolocation behavior of H. pratti via acoustic masking. The noise used in this study was in the frequency range of the bat’s communication calls and some anthropogenic noises, such as airport noise ( Wang et al, 2022 ) and traffic noise ( Geipel et al, 2019 ). Although the bats are used to and resilient to their communication calls, the constant anthropogenic noise could have stronger effects on the biosonar system of the bats.…”
Section: Discussionmentioning
confidence: 99%